Monoclonal antibodies against the complement control protein Factor H (β1 H). Issue 12 (December 1983) - Sim, E.; Palmer, M. S.; Puklavec, M.; Sim, R. B.
Abstract : Two mouse monoclonal antibodies against the human complement control protein, Factor H (β1 H), are described. The antibodies are both IgG − γ1 - subclasses and are directed against different epitopes on the human Factor H molecule. One of the antibodies, MRC OX 24, increases the cofactor activity of Factor H in Factor I-mediated cleavage of soluble C3b. The second antibody, MRC OX 23, which has no effect alone, reduces the increase in cofactor activity observed in the presence of the first antibody. However, MRC OX 24 inhibits the binding of 125 I-labelled Factor H to surface-bound C3b (EAC3b). Again MRC OX 23 alone does not have any effect but decreases the inhibition in 125 I-Labelled Factor H binding to EAC3b observed with MRC OX 24. These studies show clearly that the interaction of Factor H with soluble C3b is different to its interaction with surface-bound C3b. In an indirect immunoprecipitation system using these monoclonal antibodies, single-chain molecules of 150 000 mol. wt. are specifically precipitated from human serum and also from the sera of other primates - rhesus monkey, cynomolgus monkey, and African green monkey. There was no precipitation from sera of cow, pig, sheep, chick, or rabbit. Using a radioimmunoassay with radiolabelled monoclonal MRC OX 23, the concentration of Factor H in human plasma was determined.